Firm Size, sales growth, profitability dan firm value pada sektor basic industry and chemical - Alfinur Alfinur; Candra Wahyu Hidayat (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2021)
This study aims to explain the effect of firm size, sales growth, and profitability on firm value in manufacturing companies in the basic and chemical fields. The sampling technique using the purposive sampling technique was obtained by 40 companies in the basic and chemical fields listed on the Indonesia Stock Exchange (IDX). This type of research is quantitative research, using secondary data in the form of company financial statements obtained from www.idx.co.id, and multiple linear regression data analysis techniques. The results of this study indicate that firm size and profitability affect firm value, while sales growth does not affect firm value.